2019
DOI: 10.1590/1807-1929/agriambi.v23n7p518-523
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of beet cultivars as a function of phosphorus fertilization

Abstract: The lack of phosphorus in soil affects the development and productivity of plants; however, in order for them to express the full potential, it is necessary to supply this nutrient. The objective of this study was to define adequate doses of phosphorus, which maximize the productivity and quality of four beet cultivars, and to identify among them the most efficient use of phosphorus. The experiment was carried out at the Rafael Fernandes Experimental Farm, of the Federal Rural Semi-Arid University, Mossoró, RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
6
1
Order By: Relevance
“…The difference between the 2019 and 2021 yields was possibly influenced by phytosanitary problems that resulted in the loss of plants at the end of the cycle of the first experiment. Compared with results obtained by other authors, 25.40 t ha -1 (Silva et al, 2019) and 21.94 t ha -1 (Batista et al, 2016) in the same experimental area, lower yield was found in 2019, while in 2021 it was higher, even being close to the national average, which varies between 35 and 50 t ha -1 (Trani et al, 2018).…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…The difference between the 2019 and 2021 yields was possibly influenced by phytosanitary problems that resulted in the loss of plants at the end of the cycle of the first experiment. Compared with results obtained by other authors, 25.40 t ha -1 (Silva et al, 2019) and 21.94 t ha -1 (Batista et al, 2016) in the same experimental area, lower yield was found in 2019, while in 2021 it was higher, even being close to the national average, which varies between 35 and 50 t ha -1 (Trani et al, 2018).…”
Section: Resultscontrasting
confidence: 53%
“…Plowing and harrowing of the soil were carried out before preparing the beds. 190 kg ha -1 of P 2 O 5 was applied in the form of single superphosphate (18% P 2 O 5 , 16% Ca and 10% S) (Silva et al, 2019), seven days before planting. Topdressing fertilization was carried out via fertigation with split applications of 120 kg ha -1 of nitrogen and 180 kg ha -1 of K 2 O, 13.7 kg ha -1 of magnesium, 47.25 kg ha -1 of calcium and, only in 2021, 18.26 kg ha -1 of sulfur.…”
Section: Methodsmentioning
confidence: 99%
“…In other vegetables, the responses were also positive for dry matter production as a function of phosphate fertilization, as in carrots (Assunção et al, 2016), beetroot (Silva et al, 2019) and potatoes (Fernandes et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg) (g kg −1 ), and Zn (mg kg −1 ) contents in the nutritional status diagnosis leaf (NSDL) of beet were determined at 55 DAS [27]. The leaves were cleaned in distilled water, dried in an oven with closed air circulation at 65 • C until they reached a constant mass, and then crushed in a Willey-type mill with a 1 mm mesh sieve.…”
Section: Variables Analyzedmentioning
confidence: 99%